Exporting Firms and the Demand for Skilled Tasks - Brambilla, Irene; Lederman, Daniel; Porto, Guido (World Bank, Washington, DC, 2018)
This paper explores the link between exports and the demand for skilled tasks. Using the Chilean Encuesta Nacional Industrial Anual (ENIA), an annual census of manufacturing firms, the analysis first shows that Chilean exporters utilize more skills than Chilean non-exporters. More importantly, there is a distinct pattern of task differentiation among exporters both within skilled and unskilled tasks. Exporting firms demand the services of skilled specialized workers (engineers) as opposed to skilled administrative workers and managers. In addition, exporters demand less unskilled labor, especially blue-collar operatives. This suggests that exporters substitute skilled engineers for unskilled blue-collar workers to perform export-related tasks.